Evidence of behaviour change following a hygiene promotion programme in Burkina Faso - Curtis Valerie; Kanki Bernadette; Cousens Simon; Diallo Ibrahim; Kpozehouen Alphonse; Sangaré Morike; Nikiema Michel (The World Health Organization, 2001)
OBJECTIVES: To determine whether a large, 3-year hygiene promotion programme in Bobo-Dioulasso, Burkina Faso, was effective in changing behaviours associated with the spread of diarrhoeal diseases. The programme was tailored to local customs, targeted specific types of behaviour, built on existing motivation for hygiene, and used locally appropriate channels of communication. METHODS: Two population surveys recorded the coverage of the programme among target audiences (mothers of children aged 0-35 months). Four surveys were carried out: three prior to the programme and one in 1998 (after the programme had been running for 3 years), using structured observation of hygiene behaviours in the participants? homes to document changes in target behaviours. FINDINGS: After the programme had run for 3 years, three-quarters of the mothers targeted had had contact with programme activities. Half could cite the two main messages of the programme correctly. Although the safe disposal of children?s stools changed little between 1995 and 1998 (80% pre-intervention, 84% post-intervention), hand-washing with soap after cleaning a child?s bottom rose from 13% to 31%. The proportion of mothers who washed their hands with soap after using the latrine increased from 1% to 17%. CONCLUSION: Hygiene promotion programmes can change behaviour and are more likely to be effective if they are built on local research and use locally appropriate channels of communication repeatedly and for an extended time.